Desvelando a violência de gênero contra a mulher no espaço acadêmico: um estudo realizado sob a perspectiva das estudantes da UFERSA do campus Mossoró - Castro, Carla Jeane Holanda de (Universidade Federal Rural do Semi-Árido, 2018)
This is a theoretical and quantitative study that gathered data about the perspective of women students from UFERSA, Mossoró campus, on gender violence against women in the university environment, starting from a theoretical contribution to understanding the categories, gender, patriarchy and violence, as well as existing types of gender violence against women, as well as a methodological part, for a consistent presentation of the paths taken in the research. The objective of this study was to identify the types of violence against women existing in the Federal Rural Semi-Arid University, Mossoró campus, and to point out possible consequences in the civil, criminal and administrative spheres. With the collected data, through the application of the questionnaire, it was possible to know the main types of gender violence practiced against the women students of that campus, besides making possible a legal analysis of the mentioned conducts and, consequently, to indicate possible accountability. From the legal analyzes of the data, it was possible to conclude that there is gender violence against women within the UFERSA, Mossoró campus, which manifests itself as an element of patriarchy, and it is necessary to adopt university measures to deconstruct this system and enable students to stay and progress in the academic environment.
Monografia
Keywords: Violência contra a mulher; Gênero; Patriarcado; Relações universitárias; Violence against women; Gender; Patriarchy; University relations; CIENCIAS SOCIAIS APLICADAS::DIREITO